2019
DOI: 10.1111/ejn.14328
|View full text |Cite
|
Sign up to set email alerts
|

Impairments in gait kinematics and postural control may not correlate with dopamine transporter depletion in individuals with mild to moderate Parkinson's disease

Abstract: Parkinson's disease (PD) is a progressive neurodegenerative disorder caused by the loss of dopamine, an important neurotransmitter involved in regulating movement. Nuclear medicine imaging methods such as single‐photon emission computed tomography (SPECT) combined with radiotracers can obtain the density of this neurotransmitter. This reduced density leads to classic PD symptoms, such as bradykinesia, tremor and stiffness, consequently affecting walking and postural control. The aim of this study was to verify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…Unlike bradykinesia and rigidity, truncal dysfunction has been shown not to correlate with dopaminergic loss. 52 reported that the PPN oscillation was altered by a postural/locomotor situation during "ON" state. However, these dynamic state-dependent neural oscillatory changes were diminished during "OFF" state.…”
Section: P Oss Ib Le Neur Al Underpinning S For Impaired Motor-cog mentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike bradykinesia and rigidity, truncal dysfunction has been shown not to correlate with dopaminergic loss. 52 reported that the PPN oscillation was altered by a postural/locomotor situation during "ON" state. However, these dynamic state-dependent neural oscillatory changes were diminished during "OFF" state.…”
Section: P Oss Ib Le Neur Al Underpinning S For Impaired Motor-cog mentioning
confidence: 99%
“…Unlike bradykinesia and rigidity, truncal dysfunction has been shown not to correlate with dopaminergic loss 52 . These findings suggest that lesions of non‐dopaminergic neurons, such as cholinergic neurons in the pedunculopontine nucleus (PPN), 53 may also play an important role in gait and postural impairment in PD.…”
Section: Possible Neural Underpinnings For Impaired Motor‐cognitive Imentioning
confidence: 99%
See 1 more Smart Citation
“…Reductions in step length could be accompanied by a decrease in lower limb range of motion (RoM) [14,15]. A previous study evaluated lower limb RoM (sagittal plane) in people with PD without FOG and control individuals during a single gait [16]. Individuals with PD showed a reduced RoM of hips, knees, and ankles when compared to healthy controls [16].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study evaluated lower limb RoM (sagittal plane) in people with PD without FOG and control individuals during a single gait [16]. Individuals with PD showed a reduced RoM of hips, knees, and ankles when compared to healthy controls [16]. However, the correlation between spatiotemporal parameters and lower limb RoM and the effects of dual-task gait on lower limb RoM in people with FOG were not investigated yet.…”
Section: Introductionmentioning
confidence: 99%